Social facilitation and inhibition during maximum versus typical performance situation - Klehe, Ute-Christine; Anderson, Neil; Hoefnagels, Esther A. (2007)
The distinction between maximum performance (what people can do) and typical performance (what people will do) has received considerable theoretical yet relatively little empirical attention. Findings from social facilitation and inhibition suggest that the relationship between performers' typical and maximum performance may not always be as straightforward as had originally been assumed. Ninety-four psychology students underwent a manipulation of their self-efficacy before doing an explaining task both under typical and maximum performance conditions. Results revealed a social inhibition effect in the maximum performance condition for participants of the low self-efficacy conditions. Implications and directions for future research are discussed.